Estudo de caso de implementação de cálculo de folha de pagamento em sistema legado usando SQL - Lemos, Emilio Carlos Lopes de (Universidade Federal Rural do Semi-Árido, 2017)
Enterprise application development requires solutions that attend the requirements of term, performance, economy, robustness, scalability and without compromising quality. However, attending all these requirements, simultaneously, has been a major challenge for development teams. Application performance deserves special attention, because the users are increasingly demanding that applications has a good operation, as quickly as possible. Based on this approach, this work presents the process of creating a new methodology to optimize the payroll of a legacy system, using primarily the SQL language to acquire the best performance of the database server.
Monografia
Keywords: Banco de Dados; Linguagem SQL; Desempenho; Otimização; Database; SQL Language; Performance; Optimization; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO